Integrity assessment of corroded pipeline using in-line inspection data - Mohamed Safian, Mohd. Aznan Shukri (2006)
Oil and gas pipeline operation is one of the highest risk systems in the industry. Any failure of the system will cause a huge impact to the environment and economy. The integrity assessment of the oil and gas pipelines in Malaysia has been focused and discussed long time ago. Formerly, the inspection and maintenance work has been made in a certain interval time in order to ensure the integrity of pipelines. Therefore, in this study, the integrity level of the pipelines has been evaluated using the present in-line inspection data (ILI). Present in line inspection data (ILI), gathered from the pipelines operator, has been analyzed by using the statistical approach to obtain the corrosion growth rate. Then using the probabilistic approach is used to predict the future corrosion rate. Finally, the present and predicted data was used in the DNV RP F101 code in order to determine the pipeline integrity. The results show that the pipeline is in a good condition for the next 19 years since from the first inspection. As a conclusion, there is no remedial work suggested to be commenced and as a recommendation the inspection interval can be extended longer in order to reduce the inspection cost.